Rhenium carbonyl complexes bearing methylated triphenylphosphonium cations as antibody-free mitochondria trackers for X-ray fluorescence imaging. Issue 16 (20th July 2021) - Schanne, Gabrielle; Henry, Lucas; Ong, How Chee; Somogyi, Andrea; Medjoubi, Kadda; Delsuc, Nicolas; Policar, Clotilde; García, Felipe; Bertrand, Helene C.
Abstract : A convenient rhenium-based multimodal mitochondrial-targeted probe compatible with Synchrotron Radiation X-ray Fluorescence nano-imaging. Abstract : Synchrotron Radiation X-ray Fluorescence (SXRF) imaging is a powerful technique for the visualization of metal complexes in biological systems. However, due to the lack of an endogenous elemental signature for mitochondria, probes for the localization of this organelle are required for colocalization studies. In this work, we designed and synthesized rhenium pyta tricarbonyl complexes conjugated to methylated triphenylphosphonium TP*P + cations as multimodal probes for the visualization of mitochondria, suitable for fluorescence and SXRF imaging and quantification. Accumulation of the methylated triphenylphosphonium TP*P + -based conjugates in cells was observed in fixed A549 cells, and the amount of mitochondrial uptake was linked to the lipophilicity of the TPP + vector. Our work highlights a convenient rhenium-based multimodal mitochondrial-targeted probe compatible with SXRF nano-imaging.